The formation of malodorous dimethyl oligosulphides in treated groundwater: the role of biofilms and potential precursors. - Franzmann, Peter; Heitz, Anna; Wajon, Johannes (Elsevier Science Ltd, 2001)
Water distributed from the Wanneroo Groundwater Treatment Plant intermittently containsdimethyl trisulphide (DMTS). The compound is responsible for a "swampy odour" in the water. DMTS production from potential precursors was insignificant in the absence of biofilms when compared with DMTS production from precursors in the presence of biofilms in a biofilm reactor. Greatest dimethyl disulphide (DMDS) and DMTS production (> 3000 ng L-1 DMTS) occurred in the reactors when supplied with methane thio-containing compounds, such as methionine, S-methyl cysteine andmethyl-3-(methylmercapto)-propionate. Abiotic DMTS production from oligosulphides also occurredthrough the addition of the methylating agents, methyl iodide or methyl-p-toluene sulphonate. Significant DMTS production also occurred with Wanneroo water that contained added w-thio-containing compounds such as cysteine (1400 ngL-1 DMTS), and 3-mercapto propionate (210 ngL-1). Biomethylation, a ubiquitous response by microorganisms for the detoxification of toxic compounds, generated DMDS/TS from biofilm oligosulphides. Biofilms exposed to the toxic compounds selenate or 2,4,6- trichlorophenol methylated oligosulphides in addition to the toxins. Sodium sulphide also stimulated DMTS production. Easily Biodegradable Dissolved Organic Carbon (BDOC) probably contributed indirectly to DMTS production by the biofilms, although whether this was a result of its stimulation of greater microbial activity or consumption of oxygen, or both, remains unresolved. Stagnation of water in the biofilm reactors also increased DMTS production, which was concomitant with depletion of oxygen concentrations in the bulk water. Many processes, such as degradation of methane thio-containing compounds, methylation of sulphides and oligosulphides, and changes in contributions of different metabolic pathways upon depletion of oxygen concentrations upon water stagnation, probably contribute simultaneously to "swampy odour" production in the distribution system.